Assessing the effectiveness of interdependent corporate sustainability choices - Simone Cenci; Matteo Burato; Marek Rei; Maurizio Zollo (npj Climate Action)
Abstract Lowering the environmental externalities of business operations while preserving firms’ value is a challenging task that involves complex sustainability decisions. These decisions require navigating highly interconnected choices of actions and goals that characterise companies’ sustainability behaviour. Here, we develop an empirical framework to investigate the implications of choice interdependence on companies’ integrated financial and environmental performance. Our results suggest that the sustainability choices of companies in energy and energy-intensive sectors emerge from effective decision-making processes and have a larger impact on performance than random allocation of actions. However, comparing the behaviour of companies in our sample with hypothetical quasioptimal (“satisficing”) choices, we observe a considerable under-performance, a low choice differentiation across the population, a significant over-investment in risk mitigation activities, and under-investment in developing innovation capabilities. Overall, our study provides a framework for evaluating companies’ contribution to a sustainable low-carbon transition and highlights critical gaps in corporates’ environmental actions.